Supermarket Promotions and Food Prices: A Note. (3rd December 2014) - Lan, Hao; Lloyd, Tim; Morgan, C. Wyn
Abstract: Using a sample comprising nearly 250, 000 weekly prices from the largest seven UK supermarket chains, this note investigates two pricing practices that have attracted public interest: the tendency for promotions to 'disguise' rises in non‐sale prices and the inflation of prices prior to sales which 'exaggerate' the discount. Analysing price dynamics before and after periods of promotional discounting results show post‐sale prices are typically lower than pre‐sale prices, contrary to the disguise hypothesis. We do, however, find evidence of exaggeration of the discount, which may potentially explain why prices fall after discounts, although the evidence is not sufficiently widespread for this to be the sole cause. Results parallel the competition authority's view of supermarket promotions and point to the useful contribution that retail price microdata might play in keeping prices in check in countries where highly concentrated retail sectors raise similar concerns.